Elucidating microstructural evolution and its effect on the mechanical properties of FSWed alumina-forming austenitic steel for power plant applications. (March 2022) - Huang, Guoqiang; Wu, Jie; Yuan, Rui; Yang, Jinxue; Cao, Fujun; Midawi, Abdelbaset R.H.; Guan, Wei; Hou, Wentao; Lu, Chenyang; Gerlich, Adrian; Shen, Yifu; Meng, Fanqiang
Graphical abstract: Highlights: Fully-austenitic welded joints of AFA steel with excellent strength-ductility synergy were successfully produced by FSW. The microstructure evolution of AFA steel during FSW with various rotational speeds was systematically studied by multi-scale characterization. The processing-microstructure-properties relationship of the resulting FSW joints was well established. Abstract: Alumina-forming austenitic (AFA) steel is considered as a promising candidate used for advanced energy systems. Fusion welding of austenitic steels usually requires the introduction of a certain delta (δ) ferrite to avoid thermal cracking, but for the AFA steel, the presence of δ ferrite will greatly accelerate the precipitation of hard and brittle sigma (σ) phase at its target service temperature. In this work, for the AFA steel with a typical composition, we demonstrated a superior capability of friction stir welding (FSW) in avoiding the formation of δ and σ phases, and developing the favorable weld microstructures under various welding conditions. The microstructure evolution of AFA steel during FSW with various rotational speeds (300–700 rpm) was studied in detail. The resulting FSW joints all exhibit higher yield strength (YS) and ultimate tensile strength (UTS) than the base metal, especially at low rotational speed, while retaining reasonable ductility, despite decreasing with reducing rotational speed. The associated relationship between the microstructure and mechanical properties of the resulting FSW joints was well correlated. This work provides an effective method to obtain the fully-austenitic welded joints of AFA steel with excellent strength-ductility synergy.